Rehabilitasi Medik pada Pasien Covid 19 - Natalia Yobeanto (Syntax Idea)
COVID-19 is a respiratory tract infection due to the Severe Acute Respiratory Syndrome Corona-Virus 2 (SARS-CoV-2) virus which can cause respiratory, physical and psychological dysfunction which can reduce the patient's functional capacity. Covid 19 which is severe and accompanied by comorbidities can cause changes in physical function and result in fatalities in mobility and daily physical activity. Physical medicine and rehabilitation medicine have an important role in increasing the functional capacity of COVID-19 patients. This literature review aims to find out how to increase knowledge about the role of medical rehabilitation in COVID-19 patients and as a reference for conducting further research. This type of research includes literature reviews using PubMed and Google Scholar with articles in English and Indonesian using the keywords, namely COVID-19 rehabilitation and SARS-CoV-2 rehabilitation. Data selection based on inclusion and exclusion criteria obtained six literatures. The results of the study indicate that early rehabilitation should be given to inpatients with COVID-19. Patients with limited mobility due to quarantine or lockdown should receive an exercise program to reduce their risk of weakness, sarcopenia, cognitive decline and depression. Telerehabilitation may be the first choice for individuals at home. The conclusion of this study is that proper early rehabilitation can reduce the consequences of decreased capacity.